1993
DOI: 10.1135/cccc19931761
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Interactions in Binary Mixtures of 2-Methoxyethanol with Alkyl and Aryl Esters at 298.15, 303.15 and 308.15 K

Abstract: Densities, viscosities, refractive indices, and sound velocities of 2-methoxyethanol + ester mixtures have been measured at 298.15, 303.15 and 308.15 K. These data have been used to calculate excess volume, excess isentropic compressibility, excess refraction, excess viscosity and excess Gibbs energy of activation of flow. These quantities have been fitted to quadratic equations to estimate the parameters and standard errors. The results have been interpreted in term of the intermolecular interactions between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…The detailed TDR data analysis procedure was reported [10,11]. The thermostat (ESCY IC 201) was used to maintain constant temperature in the sample cell with an accuracy of ±0.5 K. n D 1.3550 1.3550 12 1.3960 1.3949 14 1.4020 1.4017 16 1.4130 1.4132 16 The frequency dependent values of permittivity (ε') and dielectric loss (ε") of Methyl acetate (MA) with 2-Alkoxyethanols mixtures at 308.15K are shown in Fig. 1 and Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The detailed TDR data analysis procedure was reported [10,11]. The thermostat (ESCY IC 201) was used to maintain constant temperature in the sample cell with an accuracy of ±0.5 K. n D 1.3550 1.3550 12 1.3960 1.3949 14 1.4020 1.4017 16 1.4130 1.4132 16 The frequency dependent values of permittivity (ε') and dielectric loss (ε") of Methyl acetate (MA) with 2-Alkoxyethanols mixtures at 308.15K are shown in Fig. 1 and Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The solvents n -hexane (99.5%), hexan-1-ol (99.9%), and methylbenzoate (MB, 99.9%), of the highest purity commercially available, were used without further purification. The purity was assessed by gas chromatography (GC) with a Perkin- Elmer 990 gas chromatograph, equipped with a Hewlett-Packard 3390A integrator, and also by comparing the densities, viscosities, and refractive indices with literature values (Supporting Information, Table S1, refs −30 contained therein). The pure liquids were degassed with ultrasound for several days before use and kept out of the light over Fluka Union Carbide 0.4 nm molecular sieves.…”
Section: Methodsmentioning
confidence: 99%
“…However, despite these promising properties, the scarce existing literature makes convenient a systematic research on its properties. Few studies have been reported on methyl benzoate containing mixtures, with most of them carried out at ambient pressure conditions [3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%